Nemrud Dagi : recent archaeological research and conservation activities in the tomb sanctuary on Mount Nemrud - Brijder, H. A. G. (De Gruyter, 2014)
This richly illustrated book presents in detail the sanctuaries built during the reign of Antiochus I of Commagene (ca. 75-36 BCE), including the three large tombs and ten cult places, and discusses Antiochus' rule in the context of his religious program and cult of the divine ruler. This book is the final publication of the results of the International Nemrud Da?i Project 2001-2003.